2023
DOI: 10.1021/acssuschemeng.2c06643
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Nanobubble Behaviors through Ionic Liquids during CO2 Electroreduction

Abstract: CO 2 electroreduction is a gas-consuming and -generating process, which is prevalently accompanied by the formation of bubbles. Bubbles adhered on the electrode surface severely affect the electrocatalytic efficiency. However, the formation and regulation of nanobubbles have not been studied in depth. In this work, the evolution behaviors of individual CO nanobubbles are investigated at gold nanoelectrodes, where CO is generated through CO 2 electroreduction in ionic liquids (ILs). The recorded voltammograms d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…1d, where cellulase led to a decrease in NBs particle size and an increase in their number. These findings suggested that cellulase played a role in promoting bubble formation, similar to surfactants, by easing the nucleation process and enhancing system stability (Chen et al ., 2014; Maheshwari et al ., 2018; Wang et al ., 2023). Cellulase, a natural amphipathic protein, possesses emulsifying properties that promotes in the formation of NBs.…”
Section: Resultsmentioning
confidence: 99%
“…1d, where cellulase led to a decrease in NBs particle size and an increase in their number. These findings suggested that cellulase played a role in promoting bubble formation, similar to surfactants, by easing the nucleation process and enhancing system stability (Chen et al ., 2014; Maheshwari et al ., 2018; Wang et al ., 2023). Cellulase, a natural amphipathic protein, possesses emulsifying properties that promotes in the formation of NBs.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology also facilitated the correlation of experimental data with classical and atomistic theory calculations, shedding light on overpotential-dependent nucleation rates and the critical number of atoms which comprised Ag nuclei. When this approach was extended to the nucleation of single nanobubbles, the modulation of nanobubbles in ionic liquids was examined. , These advances provide valuable insights into the dynamics and mechanisms of nanoparticle and nanobubble nucleation relevant to electrocatalysis. Furthermore, building on early works that demonstrated the voltammetric electrocatalytic investigation of single nanoparticles immobilized on nanoelectrodes, , recent reports have correlated electrocatalytic activity with structural features of single-entity electromaterials. Bimetallic nanoparticles and nickel-based metal–organic framework particles were studied for formic acid oxidation and oxygen evolution reaction (OER), respectively, demonstrating dependencies of electrocatalytic activity and turnover frequency on particle size, sheet thickness, elemental composition, and fractional coverage.…”
Section: Nanoelectrodes For Single-entity Electrochemistrymentioning
confidence: 99%
“…When this approach was extended to the nucleation of single nanobubbles, the modulation of nanobubbles in ionic liquids was examined. 16 , 17 These advances provide valuable insights into the dynamics and mechanisms of nanoparticle and nanobubble nucleation relevant to electrocatalysis. Furthermore, building on early works that demonstrated the voltammetric electrocatalytic investigation of single nanoparticles immobilized on nanoelectrodes, 18 , 19 recent reports have correlated electrocatalytic activity with structural features of single-entity electromaterials.…”
Section: Nanoelectrodes For Single-entity Electrochemistrymentioning
confidence: 99%
“…[13][14][15] Multifunctional nanoplatforms received increasing research interest in carrying nanocatalysts since they could maintain good dispersion, prevent the leaching of nanocatalysts, and endow them with easy separation characteristics. 16,17 To improve the stability and efficiency of Pd nanocatalysts, a large number of nanocarriers, such as SiO 2 , 18 metal-organic frameworks, 19 metal oxides, 20,21 polymers, 22 and Fe 3 O 4 , [23][24][25][26][27][28] have been applied for catalytically active metals. These non-toxic, easy to recover, and costeffective nanoplatforms guaranteed high efficiency for heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%